Oesophageal endoscopic ultrasound with fine needle aspiration improves and simplifies the staging of lung cancer. Issue 7 (28th June 2004) - Kramer, H; van Putten, J W G; Post, W J; van Dullemen, H M; Bongaerts, A H H; Pruim, J; Suurmeijer, A J H; Klinkenberg, T J; Groen, H; Groen, H J M
Abstract : Background: Positron emission tomography (PET) is accurate for mediastinal staging of lung cancer but has a moderate positive predictive value, necessitating pathological verification. Endoscopic ultrasonography with fine needle aspiration (EUS-FNA) is a technique for tissue verification of mediastinal and upper retroperitoneal abnormalities. The use of EUS-FNA may decrease the number of surgical procedures and thereby staging costs. Methods: EUS-FNA was used prospectively for the cytological assessment of mediastinal and/or upper retroperitoneal PET hot spots in patients with suspected lung cancer. Only if EUS-FNA was positive for malignancy was subsequent mediastinoscopy or exploratory thoracotomy cancelled. The cost effectiveness of EUS-FNA was determined. Results: Of 488 consecutive patients with suspected lung cancer, 81 were enrolled with mediastinal and/or upper retroperitoneal PET hot spots. EUS-FNA was positive in 50 (62%) patients, negative in six, and inconclusive in 25. Of the 31 negative or inconclusive patients, 26 underwent surgical staging (resulting in 14 patients with and 12 without mediastinal malignancy), while five patients had mediastinal metastases during follow up. No EUS-FNA related morbidity or mortality was encountered. The accuracy of the decision to proceed to surgery (or not) on the basis of EUS-FNA was 77% (95% CI 68 to 86). EUS-FNA detected more mediastinal abnormalities than PET except for the upper mediastinal region. Addition of EUS-FNA to conventional lung cancer staging reduced staging costs by 40% per patient, mainly due to a decrease in surgical staging procedures. Conclusion: EUS-FNA can replace more than half of the surgical staging procedures in lung cancer patients with mediastinal and/or upper retroperitoneal PET hot spots, thereby saving 40% of staging costs.